2019
DOI: 10.1007/s12224-019-09355-2
|View full text |Cite
|
Sign up to set email alerts
|

Ecological responses of semi-natural grasslands to abandonment: case studies in three mountain regions in the Eastern Alps

Abstract: Semi-natural, extensively managed, grasslands are among the most species-rich agroecosystems in Europe. However, they are threatened by abandonment. We investigated the response of semi-natural grasslands to cessation of mowing at ten sites in three UNESCO Biosphere Reserves in Switzerland and Austria. We assessed vegetation characteristics, topsoil properties and microbially mediated soil processes by comparing once-a-year mowed with adjacent long-term abandoned grasslands on semi-dry, nutrient-poor, baserich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 36 publications
1
11
0
1
Order By: Relevance
“…The nutcrackers hardly perform seed caching above the actual treeline due to deep snow (Mattes, 1982) or the lack of landmarks at high elevations (Neuschulz et al, 2017). Our results, showing missing shrub and tree invasions within exclosures are comparable to landuse changes in the Eastern Alps: formerly mown grasslands exhibited no invasion of shrubs and trees even after 60 years of abandonment (Bohner et al, 2020). Missing effects despite climate warming and grazing such as in our study area are known also from the LTER site Niwot Ridge (Scharnagl et al, 2019).…”
Section: Interaction Of Climate Warming and Grazing Effectsmentioning
confidence: 57%
See 1 more Smart Citation
“…The nutcrackers hardly perform seed caching above the actual treeline due to deep snow (Mattes, 1982) or the lack of landmarks at high elevations (Neuschulz et al, 2017). Our results, showing missing shrub and tree invasions within exclosures are comparable to landuse changes in the Eastern Alps: formerly mown grasslands exhibited no invasion of shrubs and trees even after 60 years of abandonment (Bohner et al, 2020). Missing effects despite climate warming and grazing such as in our study area are known also from the LTER site Niwot Ridge (Scharnagl et al, 2019).…”
Section: Interaction Of Climate Warming and Grazing Effectsmentioning
confidence: 57%
“…The species is known as tall herb, selectively grazed by sheep (Evju et al, 2006). The developing dominance of tall-growing herbs following grazing exclusion parallels mowing cessation effects (Bohner et al, 2020), i.e., land-use abandonment in general provokes a remarkable decrease in species richness and Shannon index. This conclusion is not new: several authors highlighted the role of grazing (or mowing) in preserving grasslands and enhancing species diversity (Olff and Ritchie, 1998;Adler et al, 2001;Austrheim and Eriksson, 2001;Dupré and Diekmann, 2001;Pavlu et al, 2005;Sebastià et al, 2008;Mayer and Erschbamer, 2017 and citations therein;Wang et al, 2017;Perotti et al, 2018).…”
Section: Decreasing Diversity In Grazing Exclusionsmentioning
confidence: 99%
“…However, Ford et al (2012) noticed that grasslands grazed extensively by cattle, ponies and rabbits had significantly greater plant species (including forb) richness than those abandoned for 6 years, while the primary productivity did not differ. A recent study (Bohner et al, 2019) concluded that long-term abandonment changed floristic composition by replacing short or shade intolerant species with medium or tallsized grasses. Also, it increased above-ground phytomass but decreased species richness.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies conclude that it decreases species richness (Janišová et al, 2020), while others (Ford et al, 2012) noticed significantly greater plant richness in grazed vs not grazed grasslands while the primary productivity did not differ. Moreover, a recent study (Bohner et al, 2019) concluded that long-term grazing cessation increased above ground phytomass but decreased species richness. Since these influences are so intricate, more case studies are necessary to clarify the effects of grazing practices on grassland parameters.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…The negative effects of this agropastoral abandonment are widely recognized as crucial issues affecting the conservation of European semi-natural grasslands [3], and are two-fold. Firstly, the lack of biomass removal in semi-natural grasslands leads to litter accumulation and the modification of plant interspecific competition [4,5]. As a consequence, a few highly competitive grasses often increase and become dominant, while less competitive species are suppressed [6,7].…”
Section: Introductionmentioning
confidence: 99%